2009
DOI: 10.3201/eid1506.080195
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-ResistantStaphylococcus aureusUSA300 Clone in Long-Term Care Facility

Abstract: We performed a longitudinal analysis of 661 methicillin-resistant Staphylococcus aureus (MRSA) isolates obtained from patients in a long-term care facility. USA300 clone increased from 11.3% of all MRSA isolates in 2002 to 64.0% in 2006 (p<0.0001) and was mostly recovered from skin or skin structures (64.3% vs. 27.0% for non-USA300 MRSA; p<0.0001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…The increase in numbers of MSSA infections was not due to an increase in the number of cultures sent, and the USA300 PFGE pattern was found for six MSSA isolates tested (691). In a long-term care facility in San Francisco, CA, as USA300 became the predominant MRSA strain to cause infections, the incidence of MRSA infections doubled from 1997 to 2006 (889). In contrast, in other geographic locales, there is little evidence that the overall incidence of invasive S. aureus infections is increasing as rapidly; instead, it appears that as the number of invasive CA-MRSA infections rise, the number of invasive infections caused by HA-MRSA is decreasing.…”
Section: Ca-mrsa: An Epidemic and Its Originsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in numbers of MSSA infections was not due to an increase in the number of cultures sent, and the USA300 PFGE pattern was found for six MSSA isolates tested (691). In a long-term care facility in San Francisco, CA, as USA300 became the predominant MRSA strain to cause infections, the incidence of MRSA infections doubled from 1997 to 2006 (889). In contrast, in other geographic locales, there is little evidence that the overall incidence of invasive S. aureus infections is increasing as rapidly; instead, it appears that as the number of invasive CA-MRSA infections rise, the number of invasive infections caused by HA-MRSA is decreasing.…”
Section: Ca-mrsa: An Epidemic and Its Originsmentioning
confidence: 99%
“…A study of (479). The presence of USA300 increased among MRSA isolates from a 1,000-bed long-term care facility in San Francisco, CA, from 11.3% in 2002 to 64% in 2006 (889). Given the complex epidemiology of CA-MRSA strains in health care settings and the circulation of HA-MRSA strains that occurs in the community, establishing a clear delineation between CA-MRSA and HA-MRSA strains has not been possible.…”
Section: What Is Community-associated Mrsa?mentioning
confidence: 99%
“…However, over the 4-year study period (2001 to 2004), there was a significant increase in the proportion of individuals harboring USA300 isolates in their nares (22). In addition, more recent data indicate that USA300 isolates are becoming a common cause of nasal carriage among U.S. hospitalized patients, especially in the southern United States (17), and continue to be a significant cause of community-acquired skin infections (35) and skin disease in long-term care facilities (45). A model of invasive MRSA infections reported by D'Agata et al indicated that MRSA isolates of PFGE type (PFT) USA300 were likely to increase in frequency in the United States and replace USA100 isolates as the most common cause of invasive MRSA infections in the future (11).…”
mentioning
confidence: 99%
“…LA-MRSA include strains such as ST398 and ST9, often carry SCCmec type V, are typically PVL negative, and (like HA-MRSA) tend to be resistant to multiple classes of antibiotics. However, both CA-MRSA and LA-MRSA have caused nosocomial infections in hospitals (Jenkins et al 2009;Fanoy et al 2009;van Rijen et al 2008, van Rijen et al 2009Kourbatova et al 2005;Seybold et al 2006;Tattevin et al 2009). …”
Section: Staphylococcus Aureusmentioning
confidence: 99%